Pengaruh kebiasaan berbahasa Jawa terhadap pemahaman konsep unggah-ungguh kelas V di gugus 02 kecamatan Bantul - Taufik Muhtarom; Aditya Hendra Sulistyawan (Universitas Sarjanawiyata Tamansiswa, 2023)
The research aims to: 1) find out the habit of speaking Javanese at home, 2) find out the understanding of the concept of ‘unggah-ungguh’ in Javanese and 3) This study aims to determine the effect of the habit of speaking Javanese at home on understanding the concept of Javanese ‘unggah-ungguh’ language in fifth grade elementary school students in Cluster 02, Bantul District. This research was conducted on fifth grade elementary school students in Cluster 02 Bantul District in the academic year 2022/2023. This study uses a quantitative survey technique with a population of 351 students with a sample of 187 students. The analysis technique uses descriptive analysis techniques, prerequisite tests, and simple linear regression analysis with a significance level of = 0.05. The results of the study: 1) The habit of speaking Javanese at home was in the high category with a percentage of 35.29%, 2) the understanding of the concept of uploading and uploading the Javanese language was in a very high category with a percentage of 51.9% and 3) there was an influence of the Javanese speaking habit in the household on understanding the concept of Javanese unggah-ungguh language in fifth grade elementary school students in Cluster 02 Bantul District with the results of the independent variable being positive and unidirectional, namely Y = 1.272 + 0.080X, with a significance value of 0.000. With the contribution of the influence of 25.40%, while the remaining 74.60% is influenced by other factors not examined in this study.